2017
DOI: 10.1016/j.addr.2017.09.017
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphic phase transitions: Macroscopic theory and molecular simulation

Abstract: Transformations in the solid state are of considerable interest, both for fundamental reasons and because they underpin important technological applications. The interest spans a wide spectrum of disciplines and application domains. For pharmaceuticals, a common issue is unexpected polymorphic transformation of the drug or excipient during processing or on storage, which can result in product failure. A more ambitious goal is that of exploiting the advantages of metastable polymorphs (e.g. higher solubility an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(51 citation statements)
references
References 147 publications
6
45
0
Order By: Relevance
“…Recent work has investigated the structural strain associated with the polymorph change that contributes to the thermosalient nature of TBB, and suggested that low-frequency vibrational modes near 43 cm –1 and 47 cm –1 are integral to the conversion 12. The importance of low-frequency vibrations for determining the properties of TBB crystals is consistent with the established relationship that exists between low-frequency lattice phonons and displacive/martensitic phase transformations as observed in other crystalline solids 23–25. In the current study, experimental low-frequency Raman spectral data (10–250 cm –1 ) was collected at various temperatures and combined with solid-state density functional theory (ss-DFT) simulations to provide clear assignments of the vibrational motions in this region.…”
Section: Introductionsupporting
confidence: 62%
“…Recent work has investigated the structural strain associated with the polymorph change that contributes to the thermosalient nature of TBB, and suggested that low-frequency vibrational modes near 43 cm –1 and 47 cm –1 are integral to the conversion 12. The importance of low-frequency vibrations for determining the properties of TBB crystals is consistent with the established relationship that exists between low-frequency lattice phonons and displacive/martensitic phase transformations as observed in other crystalline solids 23–25. In the current study, experimental low-frequency Raman spectral data (10–250 cm –1 ) was collected at various temperatures and combined with solid-state density functional theory (ss-DFT) simulations to provide clear assignments of the vibrational motions in this region.…”
Section: Introductionsupporting
confidence: 62%
“…Note that such surface effects hindering the transformation for smaller crystallites have previously been found in MD simulations of the phase transformations of molecular crystals. [28][29][30] In order to investigate this behavior on a fundamental level, we chose here Zn 2 (bdc) 2 dabco (DMOF-1) as a model system. [31] The pcu topology allows for a displacive shear transformation, [14] and even though this particular system has not been observed in a closed pore (cp) state, our force field predicts a stable cp phase, making DMOF-1 a suitable, yet simple system for our investigations, serving as a demonstrator system to develop and benchmark the methodology of nanocrystallite simulations in general.…”
Section: Doi: 101002/adts201900117mentioning
confidence: 99%
“…Clearly, such surface effects can only be considered in simulations beyond PBC. Note that such surface effects hindering the transformation for smaller crystallites have previously been found in MD simulations of the phase transformations of molecular crystals . In order to investigate this behavior on a fundamental level, we chose here Zn 2 (bdc) 2 dabco (DMOF‐1) as a model system .…”
Section: Introductionmentioning
confidence: 99%
“…Our findings are pointing towards mechanistic models based on combining information at different levels: spectroscopic imaging visualizing molecular level phenomena, such as solid-state diversity during dehydration in a single particle, combined with optical microscopy to visualize particle level phenomena, such as crack density related to this phase transformation. This can provide a basis for multiscale mechanistic models 49 and experimental validation of computer simulations. This approach would have similarities with the deep learning process in cancer diagnosis based on imaging of cellular samples 50 .…”
Section: Discussionmentioning
confidence: 99%